1987
DOI: 10.1007/bf01810577
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 5-fluorouracil infusion in refractory carcinoma of the breast

Abstract: complete remission-1/25 (4%), partial remission-7/25 (28%), stable disease-6/25 (24%), and progressive disease-11/25 (44%), for an overall response rate of 8/25 (32%). Median duration of response was 6 months. Toxicities included hand-foot syndrome, mucositis, diarrhea, and nausea and vomiting, and required treatment interruption and/or dose attenuation in 9/25 patients (36%). No myelosuppression or serious catheter-related problems were seen. We conclude that continuous 5 FU infusion is a potentially effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…In an overview of six phase II studies involving 182 patients with refractory breast cancer, most of whom were pretreated with bolus 5-FU, an average response rate of 29% (range 17-53%) has been reported (Hansen, 1991). As originally suggested in the phase I study by Lokich and subsequently confirmed by phase II studies, myelosuppression, an important toxic effect occurring with bolus administration, is rarely reported with infusional 5-FU and the dose-limiting toxicities are stomatitis, diarrhoea and plantar-palmar erythema (Lokich et al, 1981;Hansen et al, 1987;Huan et al, 1989).…”
mentioning
confidence: 99%
“…In an overview of six phase II studies involving 182 patients with refractory breast cancer, most of whom were pretreated with bolus 5-FU, an average response rate of 29% (range 17-53%) has been reported (Hansen, 1991). As originally suggested in the phase I study by Lokich and subsequently confirmed by phase II studies, myelosuppression, an important toxic effect occurring with bolus administration, is rarely reported with infusional 5-FU and the dose-limiting toxicities are stomatitis, diarrhoea and plantar-palmar erythema (Lokich et al, 1981;Hansen et al, 1987;Huan et al, 1989).…”
mentioning
confidence: 99%
“…Several studies have suggested independent improvements in the therapeutic index of both 5-FU in breast (Hansen et al, 1987;Gordon et al, 1990) and colonic (Lokich et al, 1989) cancer; and of anthracyclines in breast cancer (Gordon et al, 1990) and non-small-cell lung cancer (Valdivieso et al, 1984) using frequent low-dose scheduling. Other studies in breast cancer have shown equal efficacy and toxicity of low dose weekly anthracyclines compared with the three weekly regimens but demonstrated worsened quality of life for the weekly regimen (Twelves et al, 1991;Richards et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There has been interest recently in scheduling alterations of these agents in an attempt to produce improved response rates and increased dose AUCs while minimising acute toxicities, i.e. attempting to enhance the therapeutic index of these agents (Hansen et al, 1987;Twelves et al, 1991).…”
mentioning
confidence: 99%
“…Varios estudios han demostrado que el 5FU administrado en IC a dosis >450 mg/m 2 superficie corporal (SC) conducen a índices de respuesta superiores al 53% en primera línea de tratamiento 17,18 . En segunda línea, los índices de respuesta son de un ~30% [19][20][21][22] . El 5FU cuando se administra en IC es menos mielotóxi-co, lo que permite combinarlo con otros fármacos como la vinorelbina.…”
Section: Introductionunclassified